IMPLIKASI PENGEMBANGAN DESA WISATA TERHADAPPENINGKATAN EKONOMI MASYARAKAT LOKAL - Nur, Indrayani; Mariantha, I Nyoman; Mariantha, I Nyoman (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this research is to know the impact of the development of tourist village on the economic community in Pao village, Tombolo Pao District Gowa District, the potential of Pao village and the obstacle faced in the development of Pao village as a tourist village. The type of this research is descriptive research with qualitative approach and research type of case study. Technique of data collection is done through observation, interview and direct documentation of research object. The result of the research shows that the development of Pao village as a tourism village has a positive impact which is directly benefited by the community, such as improving the quality of human resources through awareness, training and mentoring. Training and mentoring not only improves the quality of human resources but also increases economic added value to the agricultural products of the Pao village which ultimately has implications for improving the economy of the community in a sustainable manner.